Donor-funded procurement effectiveness in the public health medical laboratory services: Examining the moderation role for government policy in donor-support - Mayavo, Crossman (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: The paper seeks to provide evidence on the government policy’s moderating role in donor-funded procurement in the laboratory services of Zimbabwe. Procurement is a key component for any organizations to function optimally and the medical laboratory service is no exception considering that the donors are the major funders of the department hence the need for this study to examine the government policy as the moderating variable for this research. Medical laboratory services plays a very important role in the functioning of any health sector as every disease have to be tested to ascertain the actual disease a person suffering from before any treatment can be commenced. Aims: The aim of the paper was to examine the moderating role of government policy on donor-funded procurement in Zimbabwe’s laboratory services. Methods: The paper made use of a quantitative method research method. Data was collected from 260 respondents sampled from a total population of 795 using RaoSoftware but only 214 respondents successfully returned the questionnaire from the Ministry of Health and Child Care, Zimbabwe and the analysis was done using STATA to run the structural equation modeling. Results: The study found out that government policy (GP) moderates the pre-donation preparation process (PDPP) (β=0.15, p-value = 0.038) donation requirement process (DRP) (β=0.24, p-value =0.000), donation recipient planning process (DRPP) (β=0.22, p-value = 0.001) and donation implementation process (DIP) (β=0.18, p-value = 0.004) and the effectiveness of donor-funded procurement. Conclusion: Based on the results, the study concluded that government policy has a role to play to support donor-funded procurement in the laboratory services in Zimbabwe and the world over and the study recommended that policy maker should take into consideration the important role as government policy plays as it support key health outcomes considering the crucial role the medical laboratory also plays. Received: 16 April 2024 | Reviewed: 22 April 2024 | Revised: 6 May 2024 | Accepted: 11 June 2024.